ANTIOXIDANT ACTIVITY TEST AND EFFECT OF ETHANOL EXTRACT OF NUSA INDA PUTIH (Mussaenda pubescens) AGAINST CREATININE, URIC ACID AND UREUM LEVELS IN WHITE RATS (Rattus novergicus) - Rolef rumondor; Rino Komalig (Indonesian Biodiversity Journal, 2021)
The purpose of this study was to examine the antioxidant activity and the effect of the extract of Nusa Indah Putih (Mussaenda pubescens) on creatinine, uric acid and urea levels in white rats (Rattus novergicus). The study design, the treatment group was divided into 5 groups. The control group (P0), the ethylene glycol group (P1), the kidney drug treatment group (P2), the Nusa Indah Putih ethanol extract group at a dose of 100 mg/kgBW (P3), and the Nusa Indah Putih ethanol extract group at a dose of 200 mg/kgBW (P4 ). Nusa Indah Putih extract has strong antioxidant activity with IC50 value of 78.27 ppm and AAI value of 1.277. Nusa Indah Putih extract was effective in lowering creatinine, uric acid and urea levels in experimental animals.